Upper Visual Field Advantage in Localizing a Target among Distractors. (April 2014) - Feng, Jing; Spence, Ian
Biases exist in many perceptual and cognitive functions. Since visual attention plays an important role in a wide range of perceptual and cognitive processes, any bias in the spatial distribution of attention is likely to be a significant source of perceptual and cognitive asymmetries. An attentional visual field task (AVF) requiring localization of a target among distractors was used to assess possible asymmetries in attentional processing in the vertical meridian. The results showed a bias favoring the upper visual field, suggesting a potentially important role of attention in perceptual and cognitive asymmetries.